Supporting Learners in a Time of Crisis - Carver, Lin B (Advances in Social Sciences Research Journal, 2020)
The COVID-19 pandemic has had a significant impact on children’s education. Because of school closures, instruction has moved online. This move to digital learning has brought with it significant barriers and challenges as evidenced by news articles and observations from teachers and students. Administrators, teachers, guidance counselors, lunch workers, business partners, and volunteers are banding together to meet the needs of students in this time of crisis.